Strategi Pemasaran Ikan Bakar Lesehan Ina Badu Ditinjau Dari Etika Bisnis Islam: Studi Kasus Lesehan Ina Badu Desa Nanga Wera Kecamatan Wera Kabupaten Bima - Inul Daratista; Ihwan P. Syamsudin; Muhammad Zia Ulhaq (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Based on the results of current observations made by researchers at Lesehan Ina Badu mantau beach Nanga Wera Village that the conditions of the past the number of customers who came were more than 50 people who came every day but the current condition that the number of customers who came was less than 20 people this is due to the large number of marketing and irregular besides that which is more important is caused by the cleanliness of the marketing place that is not well maintained, the customer's seat is less neat so that it does not provide comfort for customers, the price of fish is getting more expensive which is usually 45 / kg but the current condition the price has reached 50 / kg so this causes the trend of visitors coming to decrease every day that comes. So this study aims to determine the marketing strategy of grilled fish Lesehan Ina Badu in terms of Islamic business ethics (case study of Lesehan Ina Badu Nanga Wera Village, Wera District, Bima Regency). This research will be conducted in Nanga Wera Village, Wera District, Bima Regency, West Nusa Tenggara. This research uses Qualitative Research with a Descriptive Approach. Data Collection Techniques are Observation, Interview and Documentation. Data Analysis Techniques namely Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of this study, the marketing strategy applied by this business runs naturally and relies on a simple but deeply rooted approach.